Pediatric Multidrug-resistant Tuberculosis in Kyiv City, Ukraine - Silvia Shinpei Chiang; Yana Sheremeta; Rachel Sophie Padilla; Helen Elizabeth Jenkins; Charles Robert Horsburgh Jr; Vasyl Petrenko; Natasha Renee Rybak (Springer, 2019)
Few reports have described pediatric Multidrug-resistant Tuberculosis (MDR-TB) in the former Soviet republics, despite the fact that these countries have the highest proportion of TB cases that are MDR. We aimed to examine pediatric MDR-TB in Ukraine. This retrospective cohort study included all children <18 years of age who started undergoing MDR-TB treatment between January 1, 2011 and July 31, 2016 at Kyiv City Pediatric TB Hospital. From each child's clinical chart, we abstracted demographic and clinical data. Using Fisher's exact test, we compared characteristics between children with microbiologically confirmed vs. probable (i.e., clinically diagnosed) MDR-TB. The study population included 20 children with a median age of 5 years. At diagnosis, 12 (60%) had intrathoracic lymphadenopathy as their only radiographic abnormality, and two (10%) were asymptomatic. Children with confirmed MDR-TB were more likely to be adolescents or have radiologic abnormalities in addition to intrathoracic lymphadenopathy. Median treatment duration was 20 months. Eighteen (90%) children were treated successfully. The remaining two were transferred to another facility, and their final outcomes were unknown. The excellent outcomes in this cohort are consistent with high treatment success rates for pediatric MDR-TB reported in other parts of the world.